Anterior Knee Pain after Tibial Intramedullary Nailing - Ahmed, Junaid; Ali, Asif; Muzamil, Muhammad; Shah, Ghazanfar Ali; Sultan, Syed Akmal; Iqbal, Naveed (Biological and Clinical Sciences Research Journal, 2025)
Anterior knee pain (AKP) remains one of the most frequent and disabling complications following tibial intramedullary nailing (IMN), yet its clinical and radiographic correlates are not fully understood. Identifying risk factors and understanding long-term functional outcomes are essential for optimizing surgical technique and rehabilitation strategies. Objective: To compare pain, function, radiographic findings, and patient-reported outcomes between patients with and without anterior knee pain (AKP) after tibial intramedullary nailing (IMN), and to explore surgical/radiographic correlates. Methods: An observational cohort study was conducted at SMBBIT, Karachi, from 25 feb 2025 till 25 June 2025. Consecutive adults aged 18–45 years with tibial shaft fractures treated by IMN were enrolled after ethics approval and consent. Based on standardized pain localization, participants were classified as AKP (n=120) or no-AKP (n=120). Baseline demographics, comorbidities, and preoperative KOOS/VAS were recorded; intraoperative forms captured surgeon, nail type/size, entry point, approach, duration, and complications. Follow-ups at 1, 3, 6, and 12 months included VAS, KOOS, Lysholm, radiographs (healing, alignment, hardware issues, heterotopic ossification), additional treatments, and SF-36/satisfaction. Data were analyzed in SPSS v21 using t-tests/χ² and repeated-measures models (α=0.05). Results: Groups were demographically similar (age 30.1±6.1 vs 29.8±5.8 years; male 75.0% vs 73.3%). Preoperative VAS was comparable (4.2±1.8 vs 4.2±1.7), while KOOS was lower in AKP (45.7±11.8 vs 48.6±11.5; p=0.038). Surgical characteristics did not differ (reamed nails 80.8% vs 78.3%; infrapatellar entry 65.0% vs 62.5%; all p>0.3), except for slightly longer operative time in AKP (96.7±17.1 vs 92.1±16.5 min; p=0.034). Across all visits, AKP patients had higher pain and worse function. At 12 months, VAS was 2.4±1.0 vs 0.7±0.7, KOOS 71.5±12.5 vs 85.8±11.5, and Lysholm 72.5±6.7 vs 89.6±6.0 (all p<0.0001). Radiographic abnormalities were more frequent in AKP (17.5% vs 10.0%), with greater additional treatment use (22.5% vs 9.2%). SF-36 PCS/MCS favored no-AKP (56.8±5.7 vs 63.5±5.8; 59.9±6.2 vs 65.2±6.5; both p<0.0001) alongside higher satisfaction and less activity impact. Conclusion: AKP after tibial IMN was associated with sustained pain, inferior knee-specific function, lower quality of life, and more radiographic abnormalities despite broadly similar baseline and surgical profiles. Attention to soft-tissue preservation, implant positioning, and targeted rehabilitation may mitigate AKP.